EFEKTIVITAS PEMBERIAN HOT HERBAL COMPRESS UNTUK MEREDAKAN DISMENORE PADA REMAJA PUTRI DI SMK KESEHATAN PRIMA INDONESIA - Siti Muslima W Udi; Umi Salamah (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Hot Herbal Compress. Hot Herbal Compress is a warm compress containing natural ingredients, such as ginger, lemongrass, lemon, and champor which has an effect as a pain reliever and provides relaxation. Hot Herbal Compress is a complementary therapy that utilizes natural ingredients. One of them is to relieve pain including dysmenorrhea pain. According to the World Health Organization (WHO) in 2016 the incidence of dysmenorrhea in the world is very high, amounting to 1,769,425 people (90%) of women experience severe dysmenorrhea. While in Indonesia the prevalence of dysmenorrhea in Indonesia is 107,673 people (64.25%), consisting of 59,671 people (54.89%) primary dysmenorrhea, and 9,496 people (9.36%) secondary dysmenorrhea. Based on research data, the incidence of dysmenorrhea in West Java is quite high, namely 54.9% of women experience dysmenorrhea.Objective: To determine the effectiveness of Hot Herbal Compress against dysmenorrhea in adolescent girls in increasing the provision of alternative therapy as complementary therapy. Research Methods: This research is a quantitative research with True Experiment Design, namely Pretest-Posttest Control Group Design. In this design, there are two groups, namely the experimental group and the control group which were chosen randomly, then given a pretest to determine the initial state, is there a difference between the experimental group and the control class. The sample was divided into two groups, namely the experimental group and the control group with a research time of 1 month. The sampling technique used purposive sampling with the provision of inclusion criteria. Data analysis used paired sample t-test. Results: Based on the results of data analysis, it shows that the most respondents with an average age of 14-16 (middle adolescents) who experience dysmenorrhea are 15 respondents (50%). Based on the results of data analysis, it showed that the use of Hot Herbal Compress was effective in relieving dysmenorrhea, namely as many as 8 respondents (53.33%) did not feel dysmenorrhea after the intervention. Based on the results of data analysis, it shows that the use of warm compresses is less effective in relieving dysmenorrhea, namely as many as 9 respondents (60.00%) still feel dysmenorrhea with mild pain intensity. Based on data analysis, it is known that in the treatment group the results of the Paired Sample t-test can be concluded that there is a significant difference between the intervention group before and after treatment (p = 0.000). So, the effectiveness of giving interventions to the treatment group is larger when compared to the control group both before and after being given hot herbal compresses.